Serapan N P K Tanaman Jagung (Zea mays, L.) pada Typic Eutrudepts akibat Pemberian Pupuk Organik Padat Curah (POPC) dan Pupuk Anorganik - Yuliati Machfud; Emma Trinurani Sofyan; Daud Siliwangi Saribun; Anne Yuliana (Soilrens, 2017)
The use of organic fertilizer in the form of manure at as dose of 5000-10000 kg.ha-1 has been practiced by corn farmers, while the Solid Organic Fertilizer (SOF) in a small dose isn’t quite is known among of corn farmer. This study aims to determine the effect of POPC combined with N P K to the results of corn (Zea mays L.). The research was carried out in Typic Eutrudepts land from in October 2013 to January 2014 use a RBD, consisting of SOF was combined nine treatment with N P K and one treatment as a control. The results of this research indicated that SOF with N P K doses improved the growth and yield of corn. Increasing the dose recommended dosage 1-2 POPC (500-1000 kg.ha-1) combined with one dose of a standard N P K can increase yields significantly, the highest result was achieved by treatment with 1 dose of 2 POPC standard N P K.Keywords: corn, solid organic fertilizer, Typic Eutropepts